2009
DOI: 10.3892/ijmm_00000148
|View full text |Cite
|
Sign up to set email alerts
|

CCR5 and p53 codon 72 gene polymorphisms: Implications in breast cancer development

Abstract: Abstract. The aim of this study was to investigate the CCR5 gene and p53 codon 72 polymorphisms in a Brazilian population with breast cancer compared with healthy control subjects and to associate the clinical stage with these genotypes. No differences were detected for the D32 allele between breast cancer patients and the normal healthy donors (p=0.270), although this allele was more often present in blood donors. For p53 genotype analysis, breast cancer patients presented a significant (p<0.05) over-represen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 19 publications
1
4
1
Order By: Relevance
“…The Δ32 allele was found in 7.2% of the control subjects, compared to 2.8% in CRC patients. Our frequencies are close to those of Aoki et al in breast cancer, where Δ32 frequency was 7.77% in controls versus 3.47% in patients [39]. Given the rarity of such a mutational event, many studies did not reveal any association with the clinicopathological features, such as CRC meta-analyses where frequencies of the mutated allele in studied cases displayed no correlation [17,18].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The Δ32 allele was found in 7.2% of the control subjects, compared to 2.8% in CRC patients. Our frequencies are close to those of Aoki et al in breast cancer, where Δ32 frequency was 7.77% in controls versus 3.47% in patients [39]. Given the rarity of such a mutational event, many studies did not reveal any association with the clinicopathological features, such as CRC meta-analyses where frequencies of the mutated allele in studied cases displayed no correlation [17,18].…”
Section: Discussionsupporting
confidence: 80%
“…In this context, the impact and the results can be conflicting even in the same type of neoplasms. Some studies indicate that Δ32 polymorphism is associated with cancer risk, such as prostate [45], breast [49,50] and gallbladder cancers [51]; however, other studies have shown that there is no significant association between the mutation and cancer risk in prostate [43,52], breast [39,46,47] and lung cancers [48]. In our study, we report that mutation Δ32 reduced the risks of CRC 0.36-fold (95% CI=0.13-0.82).…”
Section: Discussioncontrasting
confidence: 47%
“…CCR5 and its ligands, particularly CCL5 have been thought to support tumor growth either directly, by driving the migration of tumor cells to tumor sites, and mostly by recruiting MDSC and dendritic cells to the tumor site [ 96 , 97 , 98 , 99 , 100 ]. Many studies showed a clear link between CCR5 and CCR5 ligands polymorphism or differential gene signature and several cancer diseases, among them: prostate cancer, breast cancer, glioblastoma, myeloid leukemia, pancreatic adenocarcinoma, Non-Small Cell Lung Cancer (NSCLC), metastatic melanoma, metastatic colorectal cancer and others [ 98 , 99 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 ]. Following Balistreri et al [ 129 ] that observed a very low prevalence of prostate cancer in men with CCR5 delta 32 mutations, which also confers HIV resistance, we have used mice lacking CCR5 to uncover the contribution of CCR5 to the cancer resistance and found that in these mice accumulation of MDSC at the tumor site is inadequate [ 130 ].…”
Section: Key Chemokine-chemokine Receptor Interactions That Support Tumor Growthmentioning
confidence: 99%
“…The migration of regulatory immune cells to tumor sites can create an immunosuppressor environment proper for cancer development. Also, cancer cells can subvert the anti-tumor action of chemokine-ligand interactions (187)(188)(189)(190)(191). Of note, CD4+ T cells are important modulators of the immune response, acting as drivers for the action of effector cells.…”
Section: Ccr5d32 In Cancermentioning
confidence: 99%
“…Aoki et al (188) assessed the CCR5D32 frequency in individuals with breast cancer and healthy women. However, no significant difference was observed between groups.…”
Section: Ccr5d32 In Cancermentioning
confidence: 99%